Pengaruh Kelengkapan Produk dan Harga terhadap Loyalitas Konsumen pada CV. Pramita Kediri - Supriyadi, Andy; Nur Hidayati; Nur Ali Agus (Jurnal Bisnis Islam dan Kewirausahaan, 2024)
This research aims to determine the influence of product completeness (X1) and price (X2) variables on consumer loyalty (Y) at CV. Pramita Kediri. This type of research is quantitative research which is used to test the relationship of a variable to other variables which emphasizes the analysis on numbers processed using statistical methods. The data collection techniques used are primary data and secondary data. Sample selection used a purposive sampling method, the number of samples in the study was 83 respondents from CV. Pramita Kediri. This research data was obtained through questionnaires, interviews and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. From the results of the research, it shows that the variables Product Completeness and Price influence Consumer Loyalty to CV. Pramita Kediri. The research results showed that the multiple linear regression equation Y = 5.569 + 0.574 Price has a partially significant effect on consumer loyalty with a sig result of 0.000 < 0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that product completeness and price have a simultaneous and significant effect on consumer loyalty to CV. Pramita Kediri.